Childhood adversity and co-occurring post-traumatic stress and externalizing symptoms among a predominantly low-income, African American sample of early adolescents. (20th February 2023) - Thompson, Erin L.; O'Connor, Kelly E.; Farrell, Albert D.
Abstract: Although there is strong evidence supporting the association between childhood adversity and symptomatology during adolescence, the extent to which adolescents present with distinct patterns of co-occurring post-traumatic stress (PTS) and externalizing symptoms remains unclear. Additionally, prior research suggests that experiencing nonviolent, negative life events may be more salient risk factors for developing some forms of psychopathology than exposure to violence. The current study used latent profile analysis to identify subgroups of early adolescents with distinct patterns of PTS, physical aggression, delinquency, and substance use, and examined subgroup differences in exposure to three forms of violent and nonviolent childhood adversity. Participants were a predominantly low-income, African American sample of 2, 722 urban middle school students ( M age = 12.9, 51% female). We identified four symptom profiles: low symptoms (83%), some externalizing (8%), high PTS (6%), and co-occurring PTS and externalizing symptoms (3%). A higher frequency of witnessing violence was associated with increased odds of membership in subgroups with externalizing symptoms, whereas a higher frequency of nonviolent, negative life events was associated with increased odds of membership in subgroups with PTS symptoms. Interventions aimed to address childhood adversity may be most effective when modules addressing both PTS and externalizing symptoms are incorporated.